Study of soliton propagation inside optical fiber for ultra-short pulse - Hasan, Mahmudul; Ahmed, S. N. Shayokh; Mohiuddin, Md. Khawza (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.